Pengaruh perceived food quality, service quality, quality of the physical environment, price fairness terhadap revisit intention dengan satisfaction sebagai variabel intervening - Tania Dwipa Siswara; Abror Abror (Jurnal Kajian Manajemen dan Wirausaha, 2022)
AbstrakPurpose - This study analyzes: (1) the effect of perceived food quality on revisit intention (2) the effect of service quality on revisit intention (3) the effect of quality of the physical environment (4) the effect of price fairness on revisit intention (5) the effect of perceived food quality on satisfaction (6) the effect of service quality on satisfaction (7) the effect of quality of the physical environment on satisfaction (8) the effect of price fairness on satisfaction (9) the effect of satisfaction on revisit intention (10) the effect of perceived food quality on revisit intention through satisfaction (11) the effect of service quality on revisit intention through satisfaction (12) the effect of quality of the physical environment on revisit intention through satisfaction (13) the effect of price fairness on revisit intention through satisfaction.Methodology - This type research is causative research. The population in this study were Padang city people who had been to Cisangkuy, Padang city. By using purposive sampling we us 300 customers as the respondent. This study used online questionnaires as the data collection instrument, This study analyzed the data by using structural equating modeling (SEM) with smart PLS 3.0 as the software package.Finding - he result of his study indicate that: (1) there is no significant effect between perceived food quality on revisit intention (2) there is no significant effect between service quality on revisit intention (3) there is no significant effect between quality of the physical environment on revisit intention (4) price fairness has a significant effect on revisit intention (5) perceived food quality has a significant effect on satisfaction (6) service quality has a significant effect on satisfaction (7) quality of the physical environment has a significant effect on satisfaction (8) price fairness has a significant effect on satisfaction (9) satisfaction has a significant effect on revisit intention (10) perceived food quality has a significant effect on revisit intention through satisfaction (11) service quality has a significant effect on revisit intention through satisfaction (12) quality of the physical environment has a significant effect on revisit intention through satisfaction (13) price fairness has a significant effect on revisit intention through satisfaction.Keyword: perceived food quality, service quality, quality of the physical environment, Price fairness, satisfaction, revisit intention.